Cross-talk between mitophagy pathways in pre-eclampsia and gestational diabetes mellitus: a systematic analysis of shared molecular mechanisms - Lidan He; Lin Lu; Xia Zhang; Xiuyan Wu; Feng Zhan; Jianbo Wu (European Journal of Medical Research)
Abstract Background Mitophagy plays a crucial role in both pre-eclampsia (PE) and gestational diabetes mellitus (GDM); however, the molecular mechanisms connecting these conditions remain unclear. This study employs bioinformatics approaches to investigate shared mitophagy-related gene signatures in PE and GDM. Methods We analyzed RNA sequencing data from PE and GDM patients to identify mitophagy-related differentially expressed genes (MRDEGs). Diagnostic models were constructed using RandomForest, LASSO and Nomogram, with validation through decision curve analysis (DCA) and calibration curves. Functional enrichment and regulatory networks involving MRDEGs, miRNAs and transcription factors (TFs) were constructed. Expression of key genes was subsequently validated in placental tissues through quantitative analysis. Results A total of 11 MRDEGs were identified. The LASSO model demonstrated promising diagnostic potential, achieving AUC values of 0.646 for PE and 0.721 for GDM. Eight key MRDEGs were closely associated with oxidative phosphorylation and reactive oxygen species (ROS) signaling pathways. Immune infiltration analysis revealed significant alterations in immune cell infiltration levels in both PE and GDM placental tissues, particularly manifesting as notable decreases in activated CD4 T cells and activated dendritic cells. These MRDEGs interacted with 80 TFs and 101 miRNAs in comprehensive regulatory networks. Finally, validation in placental tissues from control (n = 24) and disease groups (PE: n = 18, GDM: n = 20) confirmed significant differential expression of five key genes (MRPS5, PNPO, ARRB2, UBE2M, and PRAGC; all P < 0.01). Conclusions This study highlights key MRDEGs as potential diagnostic biomarkers for PE and GDM, with their differential expression substantiated in placental tissues. Mitophagy likely contributes to disease pathogenesis through immune regulation and oxidative stress mechanisms, offering novel perspectives on potential therapeutic targets.